Gerontotechnology for fall prevention of the elderly with Parkinson - Juliana Martins Ferreira; Karina Silveira de Almeida Hammerschmidt; Josiane Steil Siewert; Angela Maria Alvarez; Melissa Orlandi Honório Locks; Ivonete Teresinha Schülter Buss Heidemann (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to develop the gerontological nursing care process among the elderly with Parkinson's disease, aiming at the promotion of health through the creation of gerontotechnologies for fall prevention. Method: Convergent Care Research was used as a methodological route. Data were collected from February to October 2017, with the participation of nine elderly people with Parkinson's disease. An educational booklet, a memory game called "não cai istepô", a memory game called "caiu de maduro" were developed through clinical evaluation through scales, recorded semi-structured interview and workshops. Results: the application of gerontotechnology resulted from the elderly in self-care, empowerment and knowledge through play, revealing interest in behavior change, independence and learning, as well as serving as a facilitator of care. Conclusion: the gerontotechnologies presented as a playful and innovative instrument for the nursing gerontological care process.